Jual Beli Online Perspektif Hukum Islam - B, Umar; M, Misbahuddin; Suhufi, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The main problems of this research are 1) What is the meaning of online buying and selling? 2) How is online buying and selling implemented? 3) What is the Law on Online Buying and Selling in Islamic Law?. In this research, the author utilizes a qualitative research model, the author's technique for collecting data is by utilizing reading sources from books, journals and websites. Which I then analyzed and put it in written form. E-Commerce is a process of buying and selling products electronically by consumers and from company to company with computers as intermediaries for business transactions. The media that can be used in E-Commerce activities is the world wide web internet. The implementation of online buying and selling is that online sales and purchases are often only based on trust, which means that the perpetrators of online buying and selling are often not clearly known, so that quite a few of these buying and selling models end in fraud. For more details regarding the implementation of online buying and selling, it can be explained in detail as follows: implementation of transactions (contracts) in online buying and selling, payments in online buying and selling, delivery of goods, online buying and selling locations, online buying and selling components. When viewed from its operational system, e-commerce according to contemporary jurisprudence is a tool, media, technical method or facility (wasilah) which according to sharia rules is flexible, dynamic and variable. This includes undisciplined dunya (worldly technical issues) during the corridor of sharia for Muslims to master and utilize developments of the times for common prosperity. According to the rules of fiqh as stated by Wahbah Zuhaili, the basic principles of muamalah transactions and the conditions related to them are permissible as long as they are not prohibited by the sharia or contrary to the propositions.